Stability of the different AlOOH phases under pressure. (13th April 2016) - Cedillo, Andrés; Torrent, Marc; Cortona, Pietro
Abstract: The pressure effects on three different AlOOH structures ( α, γ, and δ phases) are systematically analyzed by density functional theory with different exchange and correlation energy functional approximations, namely two local, two generalized-gradient approximation (GGA), and two GGA for solids (GGAsol). Phase stability, compressibility and hydrogen bond evolution are studied in a range of pressures from 0 to 30 GPa. In general, the use of GGAsol functionals is mandatory in order to have the correct phase stability order, a good description of the hydrogen bonds, and a close agreement with the experimental lattice parameters at the various pressures. Pressure-induced hydrogen-bond symmetrization is found in γ and δ phases at high compression, while the hydrogen bonds in the α phase remain asymmetric. A detailed analysis of the uncertainties on the values of the bulk moduli and their pressure derivative at zero pressure deduced by fitting calculated or experimental ( P, V ) data is also presented.